Online Lending: Choice or Threat A Review of Sharia Law - Jastacia, Bella; Najmuddin, Arel Raghib (Institut Agama Islam Negeri Kendari, 2024)
The prevalence of online lending in the financial industry has surged due to its convenient accessibility to funding sources, while it also entails significant dangers. The objective of this study is to provide a thorough risk evaluation pertaining to online lending, with specific focus on the hazards that generate public apprehension. As part of a comprehensive study strategy, we conducted in-depth interviews with stakeholders and consumers, while also analyzing article 1 paragraph 3 of POJK 77 of 2016 and the current fatwa issued by DSN MUI (number 117/DSN MUI/II/2018) using an empirical legal approach. The primary objective of this research is to ascertain noteworthy hazards, such as extravagant interest rates, rigorous collecting policies, and ambiguous terms and circumstances. This risk assessment considers the social and economic consequences, such as the potential for heightened financial difficulties for customers and economic instability within households. In addition, the report analyzes the existing regulatory framework and identifies deficiencies in industry supervision, while offering recommendations for enhancing policy. The results of this study offer a thorough understanding of the risks linked to online lending, therefore enhancing the awareness of the general public, financial institutions, and regulatory organizations. This study not only identifies rising hazards but also examines viable solutions to mitigate them and minimize their negative effects. When successful, this study may inform policy discussions and efforts to address the issues of extensive internet lending